Korelasi kecepatan regangan dan kandungan bahan organik pada uji konsolidasi dengan metode constant rate of strain (crs) - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT The consolidation parameters, Cc. and câ, of organic soil determined from the CRS consolidation uji depend on the strain rate chosen the uji and the organic content of the soil tested. Due to that reason, it is needed to construct a correlation between the strain rate and organic content so that the right strain rate can adopted for the CRS consolidation uji method for soil with different organic content. In this study, sample was prepared by mixing kaolinite with organic soil